Coronavirus disease 2019 (COVID-19) and autoimmunity - E. L. Nasonov (Научно-практическая ревматология)
The coronavirus 2019 pandemic (coronavirus disease, COVID-19), etiologically related to the SARS-CoV-2 virus (severe acute respiratory syndrome coronavirus-2), has once again reawakened healthcare professionals’ interest towards new clinical and conceptual issues of human immunology and immunopathology. An unprecedented number of clinical trials and fundamental studies of epidemiology, virology, immunology and molecular biology, of the COVID-19 clinical course polymorphism and pharmacotherapy have been conducted within one year since the outbreak of 2019 pandemic, bringing together scientists of almost all biological and physicians of almost all medical specialties. Their joint efforts have resulted in elaboration of several types of vaccines against SARS-CoV-2 infection and, in general, fashioning of more rational approaches to patient management. Also important for COVID-19 management were all clinical trials of biologics and “targeted” anti-inflammatory drugs modulating intracellular cytokine signaling, which have been specifically developed for treatment immune-mediated inflammatory rheumatic disease (IMIRDs) over the past 20 years. It became obvious after a comprehensive analysis of the entire spectrum of clinical manifestations and immunopathological disorders in COVID-19 is accompanied by a wide range of extrapulmonary clinical and laboratory disorders, some of which are characteristic of IMIRDs and other autoimmune and auto-in-flammatory human diseases. All these phenomena substantiated the practice of anti-inflammatory drugs repurposing with off-label use of specific antirheumatic agents for treatment of COVID-19. This paper discusses potential use of glucocorticoids, biologics, JAK inhibitors, etc., blocking the effects of pro-inflammatory cytokines for treatment of COVID-19.